The Use of Open Source Software for Open Architecture System on CNC Milling Machine - Subagio, Dalmasius Ganjar; Atmaja, Tinton Dwi (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2011)
Computer numerical control (CNC) milling machine system cannot be separated from the software required to follow the provisions of the Open Architecture capabilities that have portability, extend ability, interoperability, and scalability. When a prescribed period of a CNC milling machine has passed and the manufacturer decided to discontinue it, then the user will have problems for maintaining the performance of the machine. This paper aims to show that the using of open source software (OSS) is the way out to maintain engine performance. With the use of OSS, users no longer depend on the software built by the manufacturer because OSS is open and can be developed independently. In this paper, USBCNC V.3.42 is used as an alternative OSS. The test result shows that the work piece is in match with the desired pattern. The test result shows that the performance of machines using OSS has similar performance with the machine using software from the manufacturer.Â